Eksplorasi, Pengujian, dan Identifikasi Khamir Antagonis terhadap Patogen Antraknos (Colletotrichum lagenarium) pada Semangka - Kardi Raharjo; Christanti Sumardiyono; Nursamsi Pusposendjojo; Sismindari Sismindari (Universitas Gadjah Mada, 2006)
Phyllosphere is one of habitat of yeast and the other microorganism included an antagonistic microorganism. The antagonistic yeasts have been isolated from watermelon phyllosphere on YM Agar medium. There are 30 isolates of yeast have been found. The pure culture of virulent isolate 115 of C. lagenarium used for testing the antagonistic ability of yeast isolates. Two yeast isolates namely K10 and K15 have highest ability to inhibit growth and development of C. lagenarium colony. From microscopic observation, the isolates K10 and K15 caused deflated on C. lagenarium hyphe. The result of identification of K10 is Candida sp. and K15 is Sirobasidium sp.